FRI0705 Progression of chronic damage in systemic lupus erythematosus patients after 5-year follow-up: data from a large monocentric cohort. (15th June 2017) - Leccese, I; Ceccarelli, F; Perricone, C; Massaro, L; Cipriano, E; Truglia, S; Miranda, F; Spinelli, FR; Alessandri, C; Valesini, G; Conti, F
Abstract : Background: The prevention of chronic damage represents one of the most important target in the management of patients affected by Systemic Lupus Erythematosus (SLE). About 50% of patients develop chronic damage, especially in the early disease phase, due to disease activity, treatment adverse events and comorbidities. Longitudinal studies demonstrated a progressive increase of damage, evaluated by using SLICC Damage Index (SDI). Objectives: Moving from these evidences, we aimed at evaluating the progression of chronic damage in a monocentric SLE cohort with at least 5-year follow-up and identifying the factors associated with damage progression. Methods: We analyzed 658 SLE patients diagnosed according to the ACR 1997 revised criteria, referring to a dedicated outpatient clinic. For the present analysis, we evaluated only patients with a minimum follow-up of 5 years and at least one visit per year. Clinical and laboratory data were collected in a standardized, computerized and electronically-filled form, including demographics, past medical history, comorbidities and concomitant treatments. In all patients, chronic damage was determined by using SDI, with the evaluation of 12 organ systems. Disease activity was evaluated by SLEDAI-2K. Furthermore, we calculated the number of flares during the follow-up, defined as an increase in SLEDAI-2K score ≥4 from the previous visit, with a minimum interval of 2 months between visits. Results: According with the inclusion criteria, we analyzed data deriving from 198 SLE patients (17 M/181 F, mean±SD age 46.8±12.1 years, mean±SD disease duration 131±99.7 months). At the first visit 60 patients (30.3%) showed SDI>0; in particular SDI=1 was identified in 65%, SDI=2 in 18.3%, SDI=3 in 10%, SDI=4 in 6.7%). At baseline, the presence of chronic damage was significantly associated with age (P<0.0001) and disease duration (P=0.001). After 5 years, we registered the progression of chronic damage in 69 patients (34.8%), with a significant increase of SDI values (baseline: median SDI 0.0, IQR 0–1; follow-up SDI: median 0 IQR 0–2, P=0.009). SDI progression resulted significantly more frequent in subjects with damage at baseline (55.0%) in comparison with free-damage patients (26.1%, P=0.0001, Fisher exact test). The progression of chronic damage was significantly associated with neuropsychiatric involvement (P=0.01), disease activity in terms of number of flares during the 5-year follow-up (P=0.001), concomitant anti-phospholipid syndrome (P=0.02) and arterial hypertension (P=0.001). Conclusions: In our study, we observed a progression of chronic damage in almost 30% of SLE patients after 5 years. In particular, the presence of previous chronic damage seem to be a risk factor for new damage development. Moreover, the lack of disease control and the presence of comorbidities allows damage progression. Taken together, the results of this study underline the need of a better management of SLE patients in order to prevent damage accrual. Disclosure of Interest: None declared